KEY LABORATORY MARKERS IN LIVER PATHOLOGY (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Liver diseases represent a significant medical and social problem due to their high prevalence, diversity of clinical forms, and the risk of developing severe complications. In modern clinical practice, laboratory markers serve as the main tool for early diagnosis, differential assessment, and dynamic monitoring of the course of hepatic pathology. Biochemical indicators of cytolysis, cholestasis, and the synthetic function of the liver are of key importance, along with immunological and serological markers that enable the identification of viral, autoimmune, and metabolic diseases. A comprehensive analysis of laboratory data contributes to уточнение the diagnosis, determination of disease stage, and evaluation of the effectiveness of ongoing therapy.